Challenges in obtaining services among survivors of intimate partner violence : a case study of married men in a refugee camp - Naw Hser Coo; Chatterjee, Joyee S.; Kusakabe, Kyoko; Duanghathai Buranajaroenkij; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
By and large, men are predominantly identified as perpetrators of 2Intimate Partner Violence3 (IPV), on the other hand, it is undeniable to say that they are survivors as well. Therefore, this study explores the different types of IPV against men by their wives. It further explores the societal normativity for IPV against men to access the services while living with IPV, and how challenges to obtain the service. Not only the constraints from the society but also the available services for IPV against men and their effectiveness of the services for these men as survivors. This study employs qualitative research methods particularly in-depth interviews (IDIs) and key informant interviews (KIIs). 41 respondents from the biggest Karen refugee camp in Thailand contribute to this study through online and offline interviews in Karen and Burmese languages. For IDIs, service users and non-service users of the IPV against men were interviewed to understand more on their experience of married life and the challenges to seek help. For KIIs, the duty bearers of the service were interviewed to investigate the effectiveness of the available services for men survivors.The major findings of the study are that available services are not considering the needs of the married men who are experiencing IPV. The social normativity and practices related to IPV is one of the barriers to using the services. IPV survivors have come across with the self belief in order to be 2a real man and ideal husband3 and social perception of men as perpetrators and no need for protection. These all reflect on their hegemonic masculinity. For the effectiveness of the services, the study illustrates that the available services are not in satisfaction, relevancy, sustainability and responsiveness.Therefore, the study suggests improving the services by allocating gender budgeting,reconstructing the legal system, strengthening staffs and institutions, creating livelihood opportunities and conducting peaceful family initiative and respectful communication.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Gender and Development Studies
Thesis (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Intimate partner violence -- Refugee camps -- Thailand